Defects of full-length dystrophin trigger retinal neuron damage and synapse alterations by disrupting functional autophagy. - Catalani, E.; Bongiorni, S.; Taddei, A.R.; Mezzetti, M.; Silvestri, F.; Coazzoli, M.; Zecchini, S.; Giovarelli, M.; Perrotta, C.; De Palma, C.; Clementi, E.; Ceci, M.; et al. (Cellular and molecular life sciences. CMLS, 2021)
Dystrophin (dys) mutations predispose Duchenne muscular disease (DMD) patients to brain and retinal complications. Although different dys variants, including long dys products, are expressed in the retina, their function is largely unknown. We investigated the putative role of full-length dystrophin in the homeostasis of neuro-retina and its impact on synapsis stabilization and cell fate. Retinas of mdx mice, the most used DMD model which does not express the 427-KDa dys protein (Dp427), showed overlapped cell death and impaired autophagy. Apoptotic neurons in the outer plexiform/inner nuclear layer and the ganglion cell layer had an impaired autophagy with accumulated autophagosomes. The autophagy dysfunction localized at photoreceptor axonal terminals and bipolar, amacrine, and ganglion cells. The absence of Dp427 does not cause a severe phenotype but alters the neuronal architecture, compromising mainly the pre-synaptic photoreceptor terminals and their post-synaptic sites. The analysis of two dystrophic mutants of the fruit fly Drosophila melanogaster, the homozygous DysE17 and DysEP3397, lacking functional large-isoforms of dystrophin-like protein, revealed rhabdomere degeneration. Structural damages were evident in the internal network of retina/lamina where photoreceptors make the first synapse. Both accumulated autophagosomes and apoptotic features were detected and the visual system was functionally impaired. The reactivation of the autophagosome turnover by rapamycin prevented neuronal cell death and structural changes of mutant flies and, of interest, sustained autophagy ameliorated their response to light. Overall, these findings indicate that functional full-length dystrophin is required for synapsis stabilization and neuronal survival of the retina, allowing also proper autophagy as a prerequisite for physiological cell fate and visual properties.